Superiority, competition, and opportunism in the evolutionary radiation of dinosaurs. - Brusatte, S; Benton, M; Ruta, M; Lloyd, G (2008)
The rise and diversification of the dinosaurs in the Late Triassic, from 230 to 200 million years ago, is a classic example of an evolutionary radiation with supposed competitive replacement. A comparison of evolutionary rates and morphological disparity of basal dinosaurs and their chief "competitors," the crurotarsan archosaurs, shows that dinosaurs exhibited lower disparity and an indistinguishable rate of character evolution. The radiation of Triassic archosaurs as a whole is characterized by declining evolutionary rates and increasing disparity, suggesting a decoupling of character evolution from body plan variety. The results strongly suggest that historical contingency, rather than prolonged competition or general "superiority," was the primary factor in the rise of dinosaurs.